Determinação do limiar de anaerobiose durante o exercício físico dinâmico em homens hipertensos de meia-idade: análise da resposta de variáveis cardiorrespiratórias e musculares - Otterço, Albaiza Nicoletti (2004)
Purpose: quantify the anaerobic threshold (AT), by analysis of the response of heart rate (HR), surface electromyography (SEMG) and the ventilatory and metabolic variables, using mathematical methods and compare with ventilatory visual method to estimate the aerobic ability in hypertensive middle-aged man. Methods: nine middle-aged man (56,77 ± 2,81 years), active, with arterial hypertension, no medication, subject a baseline to control for evaluate the arterial blood pressure profile, was done three times a week during two weeks, in supine, seated and stand up position. Systolic blood pressure (SBP) was recorded in the appearing as the first sound (first-phase Korotkoff), and diastolic blood pressure (DBP), as the fifth sound (fifth-phase Korotkoff). All subjects were submit a performed ramp continuous dynamic physical exercise test (RCDPET), in electromagnetic cycloergometer (Corival 400) in 4 W during 4 minutes, follow up increment of 15 or 20 W/min, until exhaustion and/or sign limit. Heart rate was collected in real time, on a beat-to-beat basis (electrocardiogram ECAFIX TC500), during all RCDPET, vastus lateralis SEMG activity was collected continuous (Lynx Tecnology Eletronic Ltd) and the ventilatory and metabolic variables VO2 e VCO2 were also collected breath-bybreath quantification of ventilatory volumes and gas exchanges (CPX/D MedGraphics). Workload, heart rate (HR), VO2, VCO2 and surface electromyography (SEMG) analysis by 5 different methods: ventilatory visual graphic method (VVM) used with gold standard, linear-linear bissegmentar mathematical model method (LLMM) applied to carbon dioxide output data and Hinkley mathematical model method applied to heart rate data (HMM-HR), VCO2 data (HMMVCO2) and RMS index of SEMG activity data (HMM-RMS), who appoint exercise level in was to detect the AT. Workload, heart rate (HR), VO2, VCO2 and surface electromyography (SEMG) were statistical analysis to non-parametric tests were selected: Friedman test for repeated measures followed by post-hoc Dunn test for multiple comparisons and Spearman correlation test was also used. Significance level was set at 5%. Results: HMM-VCO2 model present significant difference (p<0,05) when compare with four methods (MVV, MMLL, HMM-FC and HMM-RMS) for values of workload. For values of VCO2 and heart rate, HMM-VCO2 model present significant differed (p<0,05) when compare with HMM-FC and HMM-RMS models; for values of VO2, HMM-VCO2 model present significant difference (p<0,05) when compare with MMLL, HMM-FC and HMM-RMS models. The HMM-VCO2 model present for all variables minor values in relation the MVV, MMLL, HMM-FC and HMM-RMS models. It was observed no significant correlations (p>0,05) when VVM (gold standard) model was correlation with LLMM (rs=0,56), HMM-HR (rs=0,40), HMM-VCO2 (rs=0,43) and HMM- RMS (rs=0,40) in AT power output values detected by the gold standard. However, it was observed significant correlations (p<0,05) in the correlation workload and VO2 (rs=0,75), and workload and HR (rs=0,69) values when utilize VVM (gold standard) model. Conclusions: the results found in the present investigation suggest that the mathematical models were effective in detecting the response pattern changes in variables (HR, VO2, VCO2 e RMS index of SEMG activity) detecting adequately the AT and the date of workload, heart rate 30 (HR), VO2, VCO2 and surface electromyographic (SEMG) analyze the HMM-VCO2 model present for all variables minor values, and this fact can be associated to hypertensive subjects have a increases in the sympathetic nervous system outflow and than might contribute to prevalence of anaerobic metabolism in the energetic production and this fact can be associated with different skeletal muscle fiber composition, with relative preponderance of glycolytic fast-twitch (type II-b) over oxidative fast-twitch (type II-a) or slow-twitch (type I) and than might contribute to impaired aerobic metabolism. The methodological limitation in this study in no carry out the biopsy to muscle, propose the continuation this topic in this study.